Clinical research with cognitively impaired subjects: issues for nurses. - Lanter J (Dimensions of Critical Care Nursing)
Critical care nurses may be faced with assisting or conducting clinical research during their career. Also, critical care nurses frequently care for cognitively impaired patients who may become subjects in a clinical study. This article provides insight into the ethical principles in clinical research as they pertain to subjects who may have diminished ability to make their own decisions.